Impact of coronavirus disease 2019 on ENT clinical practice and training: the resident's perspective. Issue 12 (6th December 2021) - Kapoor, D; Ramavat, A S; Mehndiratta, M; Agrawal, A; Arora, V; Goel, A
Abstract: Background: The arrival of the coronavirus disease 2019 pandemic disrupted life suddenly and forcefully, and healthcare systems around the world are still struggling to come to terms with it. This paper reviews the impact of the pandemic on ENT practice and training. Methods: The present manuscript was developed as a narrative review to examine the role of otorhinolaryngologists in the management of the pandemic, and assess its impact on practice and training in the specialty. Results: Otorhinolaryngologists handle secretions of organs implicated in disease transmission, leaving them particularly vulnerable even while performing simple procedures. Although the pandemic increased skill expectations, it simultaneously reduced learning opportunities for trainees. In addition, attention to emergencies has been delayed. Further, the suspension of elective procedures has affected patients with malignancies. Conclusion: While planning service resumption, provisions need to be made for protective equipment and training; improving teleconsultation services will help provide sustainable care during further waves.